ASSESS THE ECONOMIC, ENVIRONMENTAL, SOCIAL BENEFITS OF RENEWABLE ENERGY ADOPTION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The use of renewable energy sources has become a crucial part of the movement towards a greener tomorrow. This article examines the potential social, environmental, and economic advantages of using renewable energy sources across a range of businesses. In terms of the economy, renewable energy might lead to more employment opportunities, cheaper energy prices, and greater energy security in the long run. Reducing dependence on fossil fuels and increasing diversity of energy sources achieves this. By reducing emissions of greenhouse gases, air pollution, and the quantity of natural resources that are exhausted, renewable energy is an important environmental factor in the fight against climate change. From a societal perspective, it improves public health by reducing pollution-related diseases, and it opens up access to clean energy in remote areas. Incorporating renewable energy sources not only contributes to sustainable development but also bolsters global efforts to reach climate objectives established in international frameworks like the Paris Agreement. Renewable energy presents both opportunities and challenges in many different places and industries, and this essay aims to delve more into both. To fully realize these advantages, it is crucial to back new policies and technological advancements.